2015
DOI: 10.1128/aac.00877-15
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation Caused by Clinical Acinetobacter baumannii Isolates Is Associated with Overexpression of the AdeFGH Efflux Pump

Abstract: cChronic wound infections are associated with biofilm formation, which in turn has been correlated with drug resistance. However, the mechanism by which bacteria form biofilms in clinical environments is not clearly understood. This study was designed to investigate the biofilm formation potency of Acinetobacter baumannii and the potential association of biofilm formation with genes encoding efflux pumps, quorum-sensing regulators, and outer membrane proteins. A total of 48 clinically isolated A. baumannii str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
134
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(147 citation statements)
references
References 47 publications
12
134
1
Order By: Relevance
“…This has led to the hypothesis that antibiotics may act as signaling molecules rather than outright antibacterial agents, especially in the natural environment (31). Numerous studies have provided support for this hypothesis, finding a wide variety of phenotypic changes caused by subinhibitory antibiotic concentrations (28,(32)(33)(34)(35). In certain species, up to 5% of the promoters appear to be affected (36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has led to the hypothesis that antibiotics may act as signaling molecules rather than outright antibacterial agents, especially in the natural environment (31). Numerous studies have provided support for this hypothesis, finding a wide variety of phenotypic changes caused by subinhibitory antibiotic concentrations (28,(32)(33)(34)(35). In certain species, up to 5% of the promoters appear to be affected (36).…”
Section: Discussionmentioning
confidence: 99%
“…In certain species, up to 5% of the promoters appear to be affected (36). In general, most of these responses tend to increase biofilm production, with concomitant increases in resistance to the signaling antibiotic (28,(32)(33)(34)(35)37). In A. baumannii, subinhibitory concentrations of imipenem or levofloxacinmeropenem have been shown to increase biofilm, type IV pili, and surface motility, which are associated with overexpression of the AdeFGH efflux pump (33,35,37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the adeM and carO genes seemed to be positively associated with adeJ expression. Reportedly, an increase in biofilm formation during the transition from a planktonic to a biofilm pattern in A. baumannii was accompanied by upregulation of the abaI gene [29]. Thus, we presume that tigecycline exerts antibiofilm activity via downregulation of the adeG gene to inhibit biofilm formation directly.…”
Section: Discussionmentioning
confidence: 99%
“…The high emergence rates of multidrug resistance (MDR) and extensively drug resistance (XDR) among A. baumannii isolates have led them to be considered as one of the top seven pathogens posing threats to medical and health systems (1,2). In addition to antibiotic resistance, biofilm formation is another characteristic leading to the survival of A. baumannii in the presence of antibiotics and high stresses (1)(2)(3). It was revealed that the difference in biofilm formation capacity among international clonal (IC) types of A. baumannii could affect the spreading of this microorganism (4).…”
Section: Introductionmentioning
confidence: 99%